Knowledge and practice of nurses working in adult intensive care units regarding prevention of ventilator associated pneumonia - Dangol Shrestha, Shanta; Nepal, Sushila; Maharjan, Subjana (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Ventilator-associated pneumonia (VAP) is one of the most serious hospital-acquired pneumonia which is a leading cause of mortality and morbidity. Prevention of VAP is critically dependent on knowledge and practice of Intensive Care Unit (ICU) nurses. Only adequate knowledge does not ensure good practice. Thus, the study aimed to find out the level of knowledge and practice of nurses regarding prevention of VAP. Method: A descriptive cross-sectional study was conducted from February to July 2025 in the adult ICUs of Patan Hospital after obtaining ethical approval. Enumerative sampling included 69 nurses for knowledge assessment and 47 for practice observation. Data were collected in two phases. At first, practice was observed using checklist, followed by knowledge assessment using a self-structured questionnaire. Data were analyzed using SPSS 25, and the fisher exact test was applied to examine the association between knowledge and practice. Result: Among 69 nurses, 38(55.10%) had good level of knowledge, 28(40.60%) average, and three (4.30%) poor level of knowledge. Among 47 nurses, 23(48.94%) demonstrated good level of practice and 24(51.06%) average level of practice. There was no significant association between knowledge and practice (p=0.56). Conclusion: More than half of nurses had good knowledge and less than half had good practice on VAP prevention. This study highlights a persistent gap between nurses’ knowledge and practice in VAP prevention. Despite adequate knowledge, practices were not consistently applied. The findings highlight the need for continuous training, supportive regular supervision, and a work environment that promotes adherence to VAP prevention protocols.